PENGARUH BIAYA PRODUKSI DAN BIAYA PEMASARAN TERHADAP LABA PADA PT. SUMATERA HAKARINDO MEDAN - Free Antonius Simanjuntak; Feren Daslim; Sunarji Harahap; Elidawati Elidawati (JURNAL BISNIS KOLEGA, 2019)
Abstract. The main purpose of establishing a company is to earn a profit so that the company always strives so that the profit generated is far greater than the expenditure of operational costs. There are several factors that influence earnings, one of which is costs. These costs include production costs and marketing costs. The purpose of this study is to find out and analyze the effect of production costs and marketing costs on profits at PT. Sumatera Hakarindo. The type of this research is in the form of quantitative descriptive research with data collection methods carried out by interviews and documentary studies at PT. Sumatera Hakarindo. The population in this study is financial statements from 2015-2017. The sample in this study is a monthly report in the form of production costs, marketing costs and profits from 2015-2017 which amounted to 36 samples. Data analysis technique using multiple regression analysis. The results showed that 40.2% of the profit variable was influenced by the independent variables namely production costs and marketing costs. The results of the t test (partial) and f test (simultaneous) indicate that the production costs and marketing costs affect the profit of PT. Sumatera Hakarindo. Keywords: Production Cost, Marketing Cost, Profit.